2022
DOI: 10.3389/fpls.2022.968618
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic loci conferring seed coat color based on a high-density map in soybean

Abstract: Seed coat color is a typical evolutionary trait. Identification of the genetic loci that control seed coat color during the domestication of wild soybean could clarify the genetic variations between cultivated and wild soybean. We used 276 F10 recombinant inbred lines (RILs) from the cross between a cultivated soybean (JY47) and a wild soybean (ZYD00321) as the materials to identify the quantitative trait loci (QTLs) for seed coat color. We constructed a high-density genetic map using re-sequencing technology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The results of the correlation analysis among seed traits showed that seed coat color was positively correlated with FC and StC, and negatively correlated with LC. Mendel first proposed that the seed coat color of peas is controlled by a pair of genes and considered a qualitative trait ( Myers, 2004 ), while the seed coat color of soybeans is controlled by multiple genetic loci ( Choung et al., 2001 ), and more than 30 molecular marker loci on different chromosomes that control seed coat color in soybean have been detected ( Yuan et al., 2022 ). However, few studies on the QTLs for seed coat color in faba bean have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the correlation analysis among seed traits showed that seed coat color was positively correlated with FC and StC, and negatively correlated with LC. Mendel first proposed that the seed coat color of peas is controlled by a pair of genes and considered a qualitative trait ( Myers, 2004 ), while the seed coat color of soybeans is controlled by multiple genetic loci ( Choung et al., 2001 ), and more than 30 molecular marker loci on different chromosomes that control seed coat color in soybean have been detected ( Yuan et al., 2022 ). However, few studies on the QTLs for seed coat color in faba bean have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the correlation analysis among seed traits showed that seed coat color was positively correlated with FC and StC, and negatively correlated with LC. Mendel rst proposed that the seed coat color of peas is controlled by a pair of genes and considered a qualitative trait (Myers JR 2004), while the seed coat color of soybeans is controlled by multiple genetic loci (Choung et al 2001), and more than 30 molecular marker loci on different chromosomes that control seed coat color in soybean have been detected (Yuan et al 2022). However, few studies on the QTLs for seed coat color in faba bean have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…~5000 years ago, in the eastern half of north China and disseminated to Europe and America in the 18th century [3,4]. Compared to their wild relatives, cultivated soybeans have undergone significant changes in growth habits, plant architecture, seed morphology, and composition under long-term targeted selection and improvement [5][6][7]. Cultivated soybeans display a bush-type growth habit with a stout primary stem and sparse branches, bearing large seeds that are generally prone to water absorption and germination.…”
Section: Introductionmentioning
confidence: 99%